LEA: An R package for landscape and ecological association studies - Frichot, Eric; François, Olivier; O'Meara, Brian (Methods in ecology and evolution, 2015)
Summary Based on population genomic and environmental data, genomewide ecological association studies aim at detecting allele frequencies that exhibit significant statistical association with ecological gradients. Ecological association studies can provide lists of genetic polymorphisms that are potentially involved in local adaptation to environmental conditions through natural selection. Here, we present the R package LEA that enables users to run ecological association studies from the R command line. The package can perform analyses of population structure and genome scans for adaptive alleles from large genomic data sets. It derives advantages from R programming functionalities to adjust significance values for multiple testing issues and to visualize results. This note also illustrates the main steps of ecological association studies and the typical use of LEA for analysing data sets based on R commands.